ASTE Band 10 (787–950 GHz) heterodyne receiver: System description, commissioning, and science verification. (22nd May 2022) - Asayama, Shin'ichiro; Kamazaki, Takeshi; Ishii, Shun; Ito, Tetsuya; Fujii, Yasunori; Iono, Daisuke; Gonzalez, Alvaro; Inata, Motoko; Sakamoto, Seiichi
Abstract: We report the system description and results of the commissioning and science verification (CSV) of the Band 10 (787–950 GHz) heterodyne receiver for ASTE (Atacama Submillimeter Telescope Experiment), a 10 m submillimeter telescope at the ALMA (Atacama Large Millimeter/submillimeter Array) site in Chile. The new ASTE Band 10 receiver cartridge was refurbished from a prototype ALMA Band 10 receiver with SIS mixers employing high critical current density junctions. We installed the new receiver on ASTE and carried out its CSV. The best double-sideband (DSB) system noise temperature achieved on ASTE toward the zenith was ∼1500 K (PWV ∼ 0.5  mm). As a part of CSV activities, we performed science verification observations to demonstrate ASTE Band 10 capabilities to the community. Wide-field images were successfully obtained toward the well-studied OMC-1 region with both [C i ]( 3 P2 – 3 P1 ) and 12 CO( J = 7–6) lines. In addition, we partially carried out observations toward a super star cluster RCW 38, [C i ]( 3 P1 – 3 P0 ), images of which were already obtained by ASTE. We demonstrated the capability of ASTE Band 10 observations toward bright and extended objects like giant molecular clouds.